2018
DOI: 10.1002/jlb.1a1217-480r
|View full text |Cite
|
Sign up to set email alerts
|

Trim27 confers myeloid hematopoiesis competitiveness by up-regulating myeloid master genes

Abstract: Trim27 (Zinc finger protein RFP) is a potential regulator of hematopoietic stem cells (HSC), yet its role in hematopoiesis remains elusive. Here, we investigated the roles of Trim27 in hematopoiesis by enforcing its expression in mouse and human hematopoietic stem and progenitor cells (HSPC). Ectopic expression of Trim27 in mouse fetal liver (FL) HSPC confers repopulating advantage with myeloid dominance. However, the number of HSC from Trim27 group was comparable with empty vector control group, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…To identify the primary neutrophil commitment regulatory genes, we first cloned cDNAs of CEBPE, LRG1, PRTN3 and CLEC11A into PCCL-desRed or PCCL-EGFP overexpression vectors [ 27 ], and the shRNA target sequences of these genes into plKO.1-GFP vectors. Both overexpression and shRNA knockdown experiments indicated that CEBPE, PRTN3, LRG1, and CLEC11A did not affect human neutrophil differentiation ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the primary neutrophil commitment regulatory genes, we first cloned cDNAs of CEBPE, LRG1, PRTN3 and CLEC11A into PCCL-desRed or PCCL-EGFP overexpression vectors [ 27 ], and the shRNA target sequences of these genes into plKO.1-GFP vectors. Both overexpression and shRNA knockdown experiments indicated that CEBPE, PRTN3, LRG1, and CLEC11A did not affect human neutrophil differentiation ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA of CLEC11A (NM_002975), LRG1 (NM_052 972), PRTN3 (NM_002777), CEBPE (NM_001805), CEBPE-M (U80982.1), XRCC3, TMEM176B, PBX3, MDM1, MDB3, HMGA1, ELK1, and short-ELK1 from the dsDNA of neutrophil biased progenitors was cloned into the PCCL-MND-PGK-dsRed or PCCL-MND-PGK-EGFP lentiviral vector as previously reported [ 27 ]. Knocking down the target genes in CD34 + cells was mediated by short hairpin RNA (shRNA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cell apoptosis related genes Hmgb2 [18], Ccnb1 [19], Aurka [20], Rrm1 [21], Tpx2 [22], Prc1 [23], and Pbk [24] were upregulated in NV HSC while downregulated in NA10hd HSC (Figure 5D). Genes that regulate the hematopoietic stem cell activity [25,26,27,28] including Hoxa10 , Hoxa7 , Hoxa9 , Ski , Prdm16 , Vps72 , Hoxb4 , and Akt1 were up-regulated in NA10hd HSC, while only Trim27 and Smarcc1 were up-regulated in NV HSC (Figure S3). Collectively, the above results demonstrate that NA10hd and NV conferred competitiveness on HSC by distinct mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Ma et al (2019) revealed that overexpression of TRIM27 suppresses apoptosis of esophagus cancer cells and increased their glucose uptake. Transcriptome analysis of Trim27-overexpressing myeloid progenitor cells indicated that it increased the expression of myelopoiesis regulators, myeloid proliferation-related signaling genes, and myeloid maturationrelated genes (Wang et al, 2018). MEF2C, a TF, is encoded by the member of the MADS box transcription enhancer factor 2 (MEF2) family of proteins and is known to play a role in myogenesis.…”
Section: Discussionmentioning
confidence: 99%